The Campus Canopy, 1935-02-20 - Georgia State Womans College (Valdosta State University Archives and Special Collections, 1935)
Team from Emory Visits Y.W.C.A.; Math-Science Club Presents Liquid Air Demonstration; Harmonious Living is Theme for Talk; College Library to House Display; Students Vote to Revise Honor Code; College Sends Delegates to Meet Press; Assembly Address; Human Biology Conference; Students Model for Art Class;
Georgia State Womans College. "The Campus Canopy, February 20, 1935." Vol.01, No.10. Valdosta State University Archives and Special Collections, 2018. http://hdl.handle.net/10428/2980. ### Persons Mentioned ### A. B. Lipscomb; Aline MacMahon; Alys Dawn Cullens; Ann Harding; Ann Turner; Ben Overstreet; Betty Vaughn; Bill Lopan; Bowen David; Camille Rogers; Carolyn Green; Carrol Peeples; Clara Davis Adams; Clara Louise Driskell; Daisy Daniels; David Copperfield; Dean Hawkes; Dorothy Dix; Eliot O' Hara; Evelyn May; Flora Mitchell; Frances Carpenter; Gayle Chute; George Cukor; George Shelton; Gertrude Gilmer; Gordon Camp; Guy Kibbee; Harold Punke; Henry Kate Gardner; Hilton Hutchinson; Hitler; Hoke Smith; Ida Lee Stearman; Ina Claire; J Frederick Wilson; J. A. Durrenberger; J. M. Elrod; J. S. Sloane; Jack Howell; James Cagney; James Stokes; Jeselyn Mosely; Jo Daniels; John Simon; John Sineath; Johnny Crosby; Katherine McGregor; Laura McLeod; Leo II; Leonora DuFour; Leopold II; Lincoln; Lorene Thomas; Louise Elrod; Louise Harper; Ludwig Bauer; M. Vincent; Margaret Bennett; Margaret Dalton; Margaret Hall; Margaret Lindsay; Marian Reid; Marion Reid; Marjorie Bullard; Martha Jennings; Martha Jones; Martha Sue Patter; Martiele Turner; Mary Askew; Mary Elizabeth Weatherford; Mary Katherine Wisenbaker; Michael Angelo; Pat O'Brien; Payne Whitney; Pearl Wilson; Ray Cameron; Richard Smoot; Robert L. Ripley; Robert Wiggins; Ruby Harrison; Ruth Hatcher; Ruth Jones; Sherod Dennis; Vangie Trimble; Vasco Martin; Virginia Bickley; Virginia Ingram; W. A. Cullens; Walter B. Pitkin; Walter Williams; William Hol; William Starr; William Tappen Thompson; Pheidias; ### Locations Mentioned ### Fitzgerald, Georgia; Africa; Albany, Georgia; America; Athens, Georgia; Atlanta, Georgia; Bainbridge, Georgia; Belgium; Biddeford, Maine; Boston, Massachusetts; Chapel Hill, North Carolina; Colorado River; Corcoran Gallery of Art; Europe; Florida; Georgia State Womans College; Gainesville, Florida; Georgia; Gettysburg, Pennsylvania; Hague; Homerville, Georgia; Miami; Jacksonville, Florida; Jesup, Georgia; Leesburg; London; Maine; Nashville, Georgia; Pavo, Georgia; Perry, Georgia; Rotunda; Russia; Sarasota, Florida; Savannah, Georgia; South America; Tallahassee, Florida; Thomasville, Georgia; Tifton, Georgia; Unadilla, Georgia; United States; Valdosta, Georgia; Waycross, Georgia; ### Organizations Mentioned ### Y. W. C. A.; Athletic Club; Sock and Buskin Club; Charm School; Columbia University; Cotillion Club; Dramatic Club; Emory Glee Club; Emory University; FERA; Fine Arts Club; Georgia Collegiate Press Association; Georgia State Womans College; Georgia Tech; Glee Club; Home Economics; League of Nations; Motion Picture Arts; Pan American Union; Philharmonic Club; Press Institute; Ritz; Telfair Academy; Texaco; W. S. Quinby Co; World Court;
Keywords: College student newspapers and periodicals -- Georgia -- Valdosta; Georgia State Womans College -- Students -- Periodicals; Newspapers